2009
DOI: 10.1016/s1470-2045(09)70079-8
|View full text |Cite
|
Sign up to set email alerts
|

The surgical learning curve for laparoscopic radical prostatectomy: a retrospective cohort study

Abstract: Background-We previously reported the learning curve for open radical prostatectomy, defined in terms of prostate cancer recurrence. We sought to characterize the learning curve for laparoscopic radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
2
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(184 citation statements)
references
References 13 publications
7
160
2
11
Order By: Relevance
“…Lower rates of positive surgical margins for high-volume surgeons suggest that experience and careful attention to surgical details, can improve surgical cancer control [47] and lower complication rates.…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…Lower rates of positive surgical margins for high-volume surgeons suggest that experience and careful attention to surgical details, can improve surgical cancer control [47] and lower complication rates.…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…In addition, most observational studies generally include men treated at high-volume tertiary referral centers. Since surgeon, radiotherapist, and oncology expertise, as well as hospital case volumes, affect treatment-related outcomes [18][19][20][21], results obtained in this setting might not be applicable to the general population. Unlike the majority of cancer data sets from large, highly specialized, singlecenter academic or tertiary referral institutions in the USA and Europe, registries reflect outcomes in men with PCa treated in real-world community settings.…”
Section: A Role For Pca Registriesmentioning
confidence: 99%
“…The learning curve generally needed 200-250 cases for the optimal resection margin results [20,21]. Secin et al reported that the rate of decrease in PRM was more slowly for LRP than for RRP [20].…”
Section: Discussionmentioning
confidence: 99%
“…Secin et al reported that the rate of decrease in PRM was more slowly for LRP than for RRP [20]. Additionally, Vickers et al reported that PSA failure decreased to 16% after 250 patients and to 9% after 750 patients [21]. LRP may be more difficult to learn because LRP must be operated in a two-dimensional space without a direct view of surgical space, with longer instrument and diminished haptic feedback.…”
Section: Discussionmentioning
confidence: 99%